Pengaruh Kompensasi, Pelatihan, dan Lingkungan Kerja terhadap Kinerja Karyawan melalui Motivasi Kerja pada PT Rukun Sahabat Senior Kabupaten Bogor - Mukrodi Mukrodi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a critical factor in determining organizational success, particularly in companies that rely on human resource effectiveness. This study investigates the influence of compensation, training, and work environment on employee performance through work motivation at PT Rukun Sahabat Senior, Bogor Regency. The objective of this research is to analyze both the direct and indirect effects of compensation distribution, training programs, and work environment conditions on employee performance, with work motivation as a mediating variable. A quantitative survey method was employed, using a structured questionnaire measured by a Likert scale. The sample consisted of 137 respondents selected through proportional random sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results indicate that compensation and training have a positive and significant effect on both work motivation and employee performance. Conversely, the work environment shows a negative but significant effect on both variables. Furthermore, work motivation is proven to significantly mediate the relationship between compensation, training, and work environment on employee performance, indicating its crucial role in strengthening organizational outcomes. These findings suggest that improving compensation systems, enhancing training effectiveness, and creating a supportive work environment are essential strategies to increase motivation and performance.